Exploring graffiti art as a catalyst for placemaking in Malaysian urban spaces - Jenyen, Chan; Mohd Noor, Mohd Zairul; Ma’rof, Aini Azeqa (Human Resource Management Academic Research Society, 2024)
Urban art, particularly graffiti, has the potential to transform city environments and enhance cultural identity, yet its integration into placemaking strategies in Malaysia remains underexplored. This study examines how graffiti art can be effectively incorporated into placemaking efforts to enhance urban spaces and foster community engagement. Despite its potential to foster cultural diversity and community dialogue, negative perceptions and lack of strategic frameworks hinder graffiti's acceptance as a valuable architectural element. This research aims to bridge this gap by developing comprehensive strategies and methods to integrate graffiti into placemaking initiatives. By exploring the connections between graffiti art and placemaking elements, the study seeks to transform urban spaces and enhance cultural identity in Malaysia. Expected results include improved urban aesthetics, increased community participation, and a stronger sense of local cultural identity. The study's contributions lie in providing actionable methodologies for leveraging graffiti art to create vibrant, inclusive public spaces in Malaysia.